Determinants of Audit Delay for Indonesian Property and Real Estate Companies - Sauri, Nazar Sufyan; Setiawan, Muhammad Samsul; Utama, Muhammad Fajar Satrio (Indonesian Journal of Advanced Research, 2024)
This research aims to empirically prove how factors such as audit tenure, audit opinion, solvency, and company size influence audit delay on the Indonesia Stock Exchange  in the sector of property and real estate companies for the period 2018 to 2022. The sample size for this quantitative research is 53 companies and the sampling process and criteria use the purposive sampling method. Data analysis used in this research uses panel data regression analysis. E-Views 12 to analyze data. The research results show that company size has a positive influence on audit delay, audit opinion has a negative influence on audit delay, audit tenure has no influence on audit delay and solvency has no influence on audit delay.